The Shipibo Ceremonial Use of Ayahuasca to Promote Well-Being: An Observational Study - Gonzalez, Debora; Cantillo, Jordi; Perez, Irene; Carvalho, Maria; Aronovich, Adam; Farre, Magi; Feilding, Amanda; Obiols, Jordi E.; Bouso, José Carlos (Frontiers in Pharmacology, 2021)
Promoting well-being is one of the main goals to improve health in the world. We examined the well-being and quality of life over the course of one year in a sample that participated in an Indigenous Shipibo healing program where traditional healers work in a series of ayahuasca ceremonies. We also explored the role of decentering as a mediator of psychological well-being. Participants who attended the program responded to an online survey that included a Psychological Well-Being Scale; Oxford Happiness Questionnaire; The World Health Organization Quality of Life Spirituality, Religiousness,​ and Personal Beliefs scale; the WHO Quality of Life-BREF scale; and Decentering scale. Baseline (T0) and post-assessment (T1) was completed by 200 individuals. Of these, 101 completed the follow-up assessment at three months (T2), 91 at six months (T3), and 94 at 12 months follow-up (T4) after leaving the center. ANOVAs test was performed in a representative sub-sample to control the passing of time two months before attending the program (T-1). Pearson’s test was performed to examine the relationship between psychological well-being and decentering during the period of T0 and T1. A significant increase was observed in all the scales at all time points (p ≤ 0.01). The subgroup analysis performed in a representative subsample allowed us to infer that the significant differences in outcomes are due to the effect of their stay at the center and not the passing of time. We found a relationship between decentering and the improvement of psychological well-being (r = 0.57; p < .01). Our results suggest that the Indigenous Shipibo healing work with ayahuasca has value to improve long-term well-being and quality of life for Westerners.